Arm Support for Practical Work in 6g Welding Position - Rozali, Mohd Zulfadli; Jusoh, Muhammad Nur Hakim (Research and Innovation in Technical and Vocational Education and Training, 2021)
This study aims to help assist student that undergo 6G position welding practical work. The issue is the most student who did 6G position welding practical work is their difficulty to find their rhythm to do 6G position welding in consistent way. The development of arm support for practical work in 6G welding position is to help those has weakness in conducting 6G welding position by giving support towards arm to keep stamina towards electrode with left hand help. This objective of the study is to design, develop, and test arm support to 6G position welding practical work functionality. ADDIE model was as guide to develop this tool and it stand for analysis, design, development, implementation, and assessment. Software SOLIDWORK was used to develop this product start from small development of components until combination between large part and become arm support. This software is also used as an implementation by combining every large portion and implement simulation video presentation to see tool developed functionality. Feedback from three people expert from areas of common in welding field with welding experience more than five years. This expert chosen to assess and identify functionality tool developed this. Retrieval from expert feedback result show all three experts have confirmed that support arm development to 6G position welding practical work has achieved the objective that had set. Nevertheless, this development need improve more with suggestion by experts so that this tool can be used in long period to help student that is less skilled learn.